Closed loop stimulation in patients with chronic heart failure and severe chronotropic incompetence: Responders versus non-responders. (1st January 2023) - Proff, Joachim; Merkely, Béla; Papp, Roland; Lenz, Corinna; Nordbeck, Peter; Butter, Christian; Meyhoefer, Juergen; Doering, Michael; MacCarter, Dean; Ingel, Katharina; Wolfarth, Bernd; Thouet, Thomas; et al.
Abstract: Background: Clinical effects of rate-adaptive pacing (RAP) are unpredictable and highly variable among cardiac resynchronization therapy (CRT) patients with chronotropic incompetence. Physiologic sensors such as Closed Loop Stimulation (CLS), measuring intracardiac impedance changes (surrogate for ventricular contractility), may add clinical benefit and help identify predictors of response to RAP. The objective of the present BIOlCREATE study subanalysis was to identify criteria for selection of CRT patients who are likely to respond positively to CLS-based RAP. Methods: In the randomized, crossover BIO|CREATE study, CRT patients with severe chronotropic incompetence and NYHA class II/III were randomized to CLS with conventional upper sensor rate programming or to no RAP for 1 month, followed by crossover for another month. At 1-month and 2-month follow-ups, patients underwent treadmill-based cardiopulmonary exercise test. Positive CLS response was defined as a ≥ 5% reduction in ventilatory efficiency slope. Eight of 17 patients (47%) were CLS responders. In this subanalysis, we compared responders and non-responders to explore outcomes, mechanisms, and predictors. Results: All cardiopulmonary variables, health-related quality of life, patient activity status, and NT-proBNP concentration showed favorable trend in CLS responders and unfavorable trend in non-responders, underlining the need to find predictors. Following all analyses, we recommend CLS in heart failure patients with improved left ventricular ejection fraction (LVEF >40%, after a ≥ 10-point increase from a CRT-pre-implant value of ≤40%), corresponding to 'HFimpEF' in the universal classification system. Conclusion: HFimpEF patients are likely to benefit from CLS-based RAP, in contrast to 'HFrEF' (heart failure with reduced LVEF [≤40%]). Highlights: Rate adaptive pacing (RAP) in CRT patients with severe chronotropic incompetence Physiologic Closed Loop Stimulation (CLS) sensor might increase benefits from RAP. How to predict which CRT patients will respond positively to CLS-based RAP. Heart failure patients with improved LVEF (HFimpEF) are best responders to CLS. HFimpEF: LVEF>40% and a ≥10-point increase from a CRT-pre-implant value of ≤40%.